Movements of Juvenile Green Turtles (Chelonia mydas) in the Nearshore Waters of the Northwestern Gulf of Mexico - Metz, Tasha L.; Gordon, Mandi; Mokrech, Marc; Guillen, George (Frontiers in Marine Science, 2020)
Satellite telemetry is a valuable tool for examining long-term, large scale movements of highly migratory species. Tracking data can be used by resource managers to protect habitat and ensure recovery of threatened and endangered species. Few tracking studies have focused on habitat use patterns of juvenile, neritic stage turtles. Satellite tracking surveys were conducted to assess juvenile green turtle movements in the northwestern Gulf of Mexico during 2006-2010. Fifteen turtles were equipped with platform terminal transmitters (PTT; 3 rehabilitated, 12 wild). Mean track duration was 129 days (range: 16-344 days). A hierarchical switching state-space model (hSSM) was applied to extrapolate population level foraging/resident versus migratory movements. All turtles displayed residency in Texas bays during summer months (March-November) while 5 individuals exhibited seasonal migrations into Mexican waters following passage of strong cold fronts in December and January. Winter (e.g. Mexico) versus summer (e.g. Texas) core areas were not significantly different. Winter 95% contours were significantly larger than summer (summer: 125.4 ± 47.5 km2, n = 15; winter: 274.4 ± 252.9 km2, n = 5). Space-time hot spot analysis provided a new and unique approach for conducting spatiotemporal cluster analysis, and was applied to migratory turtles to determine monthly changes in distribution and habitat associations. Changes in hot spots over time were detected within the lower regions of the Laguna Madre with punctuated intervals of hot spot activity. Upper regions of the Laguna Madre were identified as new hot spots in the later part of the year (e.g. Fall/Winter). Within core areas in Texas, seagrasses comprised an average density of 32.4% while 87.5% of the total available seagrass habitat occurred within the 95% KDE contour. Based on PTT and historic tide station surface water temperatures, all turtles tracked over winter migrations and residencies (n = 5) remained within waters > 15°C, suggesting a threshold temperature at which migration behavior may be initiated. Continued recovery of threatened and endangered sea turtle populations depends on a comprehensive examination of patterns in habitat use. These data suggest cooperation between the US and Mexico is needed to protect critical habitat and enhance recovery of this species.